Export subsidies, international food aid, export credits, export credit guarantees or insurance programmes, and agricultural exporting state trading enterprises (WTO GenevaCH, 2013)
Provides information on the use of export subsidies by Members with export subsidy commitments. Specifies information concerning export subsidy reduction commitments, both in terms of budgetary outlay and quantity commitments as well as information concerning notified export subsidy budgetary outlays and quantities.
Background paper by the Secretariat.